Wind modelling, validation and sensitivity study using Weather Research and Forecasting model in complex terrain. (April 2017) - Mughal, Muhammad Omer; Lynch, Mervyn; Yu, Frank; McGann, Brendan; Jeanneret, Francois; Sutton, John
Abstract: A physically-based wind model is applied to determine wind speed and direction and to conduct a model sensitivity analysis. The focus is the East African site of the Lake Turkana Wind Farm, characterized by complex terrain and high diurnal variability that creates a nocturnal jet of typically 15 m/s. Observations from three tall meteorological masts are compared with Weather Research and Forecast (WRF) model outputs. WRF is configured with four domains nested down to 900 m spatial resolution. The model is tested with initialization fields from two different sources, optimised using different grid configurations and parameterization schemes. Comparing model and data from 3 tall masts A, B and C yields that the primary source of error in WRF model simulation in a complex terrain is due to incorrect specification of boundary fields used to initialize the model. RMSEs achieved in this research are ≤2 m/s representing good model performance (Emery et al., 2001). Highlights: Optimized WRF configuration investigation for a complex terrain. Simulations evaluated against situ measurements at the Lake Turkana wind farm. Improved wind speed and direction prediction using ECMWF/ERA initialization fields. 87% reduction in power prediction error. The study established WRF's short term forecasting accuracy in a data sparse region.